1989
DOI: 10.1161/01.res.64.4.814
|View full text |Cite
|
Sign up to set email alerts
|

SC-39026, a serine elastase inhibitor, prevents muscularization of peripheral arteries, suggesting a mechanism of monocrotaline-induced pulmonary hypertension in rats.

Abstract: In rats injected with the toxin monocrotaline, altered synthesis and distribution of pulmonary artery elastin suggest that increased elastase activity may be important in the development of vascular changes and progressive pulmonary hypertension. To test this hypothesis, male Sprague-Dawley rats (250-300 g) were given 40 mg/kg of the elastase inhibitor SC-39026 in a carboxymethylcellulose vehicle or vehicle only by gavage, 12 hours before and twice daily for 8 days after a single subcutaneous injection of eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 24 publications
3
42
0
Order By: Relevance
“…The death rate from failing myocardium in the right ventricle as a result of MCT administration increases in a dose-dependent manner. [12][13][14][15][16][17] Hirota, et al 2) subcutaneously injected 40 mg/kg of MCT solution into rats. Two weeks later, the right ventricular systolic pressure rose to 25.4 ± 2.2 mmHg in the MCT group and to 13.3 ± 1.4 mmHg in the control group.…”
Section: Myocyte Investigationmentioning
confidence: 99%
“…The death rate from failing myocardium in the right ventricle as a result of MCT administration increases in a dose-dependent manner. [12][13][14][15][16][17] Hirota, et al 2) subcutaneously injected 40 mg/kg of MCT solution into rats. Two weeks later, the right ventricular systolic pressure rose to 25.4 ± 2.2 mmHg in the MCT group and to 13.3 ± 1.4 mmHg in the control group.…”
Section: Myocyte Investigationmentioning
confidence: 99%
“…Increased serine elastase activity has been documented in a number of clinical (2)(3)(4) and experimentally induced cardiovascular diseases (5)(6)(7)(8)(9)(10)(11). For example, elevated serine elastase activity has been reported in patients with myocardial infarction and unstable angina (4), peripheral and coronary artery disease (2), and abdominal aortic aneurysm (3).…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that an enzyme that has elastolytic properties might be involved in the pathophysiology of this poorly understood process. This was further explored in experimental rats in which progressive pulmonary hypertension was induced by injection of the toxin monocrotaline (5)(6)(7)(8)(9). There was an increased number of breaks in the internal elastic lamina observed as early as 4 d after injection of the toxin associated with the initiation of structural changes (7).…”
Section: Introductionmentioning
confidence: 99%